(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Darmawati, Mulyadi A, Suwondo, Harto S. 2021. The diversity and vegetation structure based on growth levels at an urban green campus in Pekanbaru City, Indonesia. Biodiversitas 22: 5123-5132. The Bina Widya campus of the University of Riau (UNRI), Pekanbaru, Indonesia has the green open space (GOS) in its area and there are many species of vegetation. In a green open space, variables like diversity and vegetation structure must be considered based on growth levels, this study intended to determine the composition, structure, and diversity of vegetation.The results showed that there were 33 species of trees, 29 species of poles, 16 species of saplings, and 8 species of seedlings from 44 species belonging to 22 families. There were 874 individuals which consisted of 534 trees, 207 poles, 87 saplings, and 46 seedlings. The most common species found was Swietenia macrophylla King (Meliaceae) with 289 individuals. The highest Important Value Index of vegetation species at each growth level was the tree of Alstonia scholaris (L) R.Br (300%, location IX), the pole of Hibiscus tiliaceus L. (300%, location VII), saplings of Vitex pinnata L. (300%, location IV), and S. macrophylla King (300%, locations I), seedlings of S. macrophylla King (300%, location I), and Garcinia mangostana L (300%, location IX). We did not find vegetation species at the levels of sapling or seedling in locations of II, III, V, VI, and VIII. It is necessary to replant the vegetation. The highest Species Diversity Index (H’) at location X was trees (2.34), poles (2.28), saplings (1.77), and seedlings (1.17). The average H’ vegetation at Bina Widya Campus UNRI was 2.44 (medium). Vegetation on the Bina Widya Campus is fairly steady in terms of delivering advantages for human environmental services.